2020
DOI: 10.1021/acsanm.0c01740
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Computational and Experimental Design of Ductile, Abrasion-Resistant Thermoplastic Polyurethane/Graphene Oxide Nanocomposites

Abstract: Polymer nanocomposites are widely studied for improving and developing novel materials. Incorporation of nanofillers in polymer matrices impart strong behavioral changes, with the extent of dispersion of fillers in polymers playing a key role. This not only limits the amount of filler one can incorporate but also often leads to enhancement of some material properties at the expense of others. Herein, for the first time, thermoplastic polyurethane (TPU) graphene oxide (GO) nanocomposites with improved abrasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…14 Due to its copolymer structure, TPU presents thermoplastic behavior with thermoset characteristics, that is, TPU has polyol soft segments, which give flexibility to the polymer, and polyisocyanates hard segments, which arrange themselves between chains and act as physical crosslinkers. 15 There is not, however, a wide offer of commercially available FDM 3D printing filaments with both flexibility and electrical/thermal conductivity. Few products are available, for example, filaments manufactured for 3D printing loaded with carbonaceous nanostructures, such as GNPs or CNTs, but most are still very focused on optimizing only the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Due to its copolymer structure, TPU presents thermoplastic behavior with thermoset characteristics, that is, TPU has polyol soft segments, which give flexibility to the polymer, and polyisocyanates hard segments, which arrange themselves between chains and act as physical crosslinkers. 15 There is not, however, a wide offer of commercially available FDM 3D printing filaments with both flexibility and electrical/thermal conductivity. Few products are available, for example, filaments manufactured for 3D printing loaded with carbonaceous nanostructures, such as GNPs or CNTs, but most are still very focused on optimizing only the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…From the polymers compatible with FDM 3D printing, and taking into account the desired flexibility of the final material, TPU has satisfactory mechanical properties (good toughness, characteristic of rubbery materials), and is mostly considered a biocompatible material, which allows its use in the production of wearable devices, soft robotics, and wearable sensors for extended biosignal uptake 14 . Due to its copolymer structure, TPU presents thermoplastic behavior with thermoset characteristics, that is, TPU has polyol soft segments, which give flexibility to the polymer, and polyisocyanates hard segments, which arrange themselves between chains and act as physical crosslinkers 15 …”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) exhibits excellent mechanical characteristics (tensile strength: ∼58 MPa, elongation at break: ∼1400%, Young’s modulus: ∼5–7 MPa, hardness (Shore A ∼72), durability, resistance against chemicals, environmental friendliness, etc. ). Thermoplastic polyurethane-based EMI shielding materials have several benefits including lightweight, flexibility, easy processability, and resistance to corrosion . Recently, thermoplastic polyurethane has been utilized as a matrix for various nanofillers to develop electromagnetic interference shielding nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] GO can be easily dispersed in polar solvents, including water, and is known to exhibit liquid crystallinity. [9][10][11][12] Good dispersity and the ability to form LC has enabled GO to be a good candidate as an effective nanofiller compared to other carbon materials. Therefore, one of the most attractive applications of GO is GO-based polymer nanocomposites, where GOs are employed as effective nanofillers enhancing the physical properties of the neat polymer matrix based on its large surface area and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Danda et al reported improved ductility for thermoplastic polyurethane/GO nanocomposites. 10 Kim et al reported a CNT/PVA nanocomposite in the presence of GO; the GO additives effectively facilitate the structure of an interconnected CNT network in PVA and thus CNT/GO/PVA nanocomposites exhibit higher mechanical properties than CNT/PVA nanocomposites. 9 In these applications, crystalline polymers can be additionally considered as they generally provide superior physical properties than amorphous polymers.…”
Section: Introductionmentioning
confidence: 99%